Heartwood dry extract: a key fraction for the quality and the diversity of rums and spirits. Issue 1 (9th December 2020) - Vivas, Nicolas; Picard, Magali; Bourden‐Nonier, Marie‐Françoise; Vivas de Gaulejac, Nathalie; Mouche, Claire; Rossy, Cybille
Abstract : Oak heartwood provides easily soluble dry extract. The fraction is rich in various polymers including polysaccharides, polyphenols and lignin. During cask ageing, spirit composition improves by the addition of oak dry extract. New spirits, such as white rums, develop colour and character such as softness and sweetness. Mouthfeel and presentation of the final product are completely changed. The content of alcohol and dry extract influence the thickness and taste of the spirit. Microviscosity was measured in a commercial rums and other spirits, highlighting a direct correlation between dry extract and microviscosity. Two indices are proposed for the evaluation of ageing in oak casks: the ratio of Total Polyphenols Index (TPI)/dry extract and the Global Tastefully Index integrating microviscosity and TPI. The proposed indices allowed the differentiation between (i) long aged products, (ii) short ageing and (iii) white spirits with short ageing and artificial treatments mimicking cask ageing. © 2020 The Institute of Brewing & Distilling